2019
DOI: 10.9734/sajrm/2019/v4i130095
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Screening of Antimicrobial Activities of Ocimum gratissimum on Clinical Isolates

Abstract: This study was undertaken to evaluate  the antimicrobial activities of crude  ethanol and methanol extracts of the leaves of Ocimum gratissimum L. (scent leaf) on Escherichia coli, Klebsiella  pneumoniae, Pseudomonas aeruginosa, Staphylococcus auerus and Candida albicans.The antimicrobial activities were carried out using  agar well diffusion method. The Minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC/MFC) of the plant extracts on the test isolates were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…Furthermore, it's worth noting that the ethanolic extract of Ocimum gratissimum demonstrated higher antimicrobial activity compared to the aqueous extract, is in accordance with the findings of Oshim et al, 2019, where all isolates exhibited resistance to the ethanolic extract of Ocimum gratissimum.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, it's worth noting that the ethanolic extract of Ocimum gratissimum demonstrated higher antimicrobial activity compared to the aqueous extract, is in accordance with the findings of Oshim et al, 2019, where all isolates exhibited resistance to the ethanolic extract of Ocimum gratissimum.…”
Section: Discussionsupporting
confidence: 85%
“…High mortalities of adult Tribolium were observed in the direct method application and residual application on the filter paper method, this indicated high susceptibility of this insect to these botanical insecticides. This is in line with Isman [8] in plant essential oils for pest and disease management [9], He reported that O. gratissimum having 90% of Eugenol as its active ingredient which makes it possess insecticidal properties. Also, Obeng-ofori and Reichmuth [10], demonstrated Eugenol the major constituent of the oil of O. gratissimum to be effective against four different storage pests.…”
Section: Discussionsupporting
confidence: 72%